173 ASSOCIATIONS BETWEEN CARDIOVASCULAR SIGNAL ENTROPY AND FUTURE FALLS, SYNCOPE, AND FEAR OF FALLING. (25th October 2022) - Knight, SP; Davis, J; Duggan, E; Kenny, RA; Romero-Ortuno, R
Abstract: Background: Previous studies have reported impaired blood pressure (BP) control during standing to be associated with future falls and syncope. Increased complexity in BP signals has been shown to be associated with poorer cognitive performance, frailty, and increased mortality risk. The aim of this study was to investigate associations between the level of complexity in beat-to-beat BP data during an active stand challenge and future occurrence of falls, syncope, and fear of falling in a cohort of older adults from The Irish Longitudinal Study on Ageing (TILDA). Methods: Beat-to-beat BP was continuously measured during an active stand protocol at wave 1 of TILDA (2009-2011). Complexity of BP signals was quantified using sample entropy (SampEn) during rest, stand, and recovery sections of data. Self-reported occurrences of falls, syncope, and fear of falling were collected at waves 2 to 6 (2012-2021). Comprehensively controlled modified Poisson modelling was employed to investigate associations. Results: Complete data were available for 4714 individuals (age: 61.0±8.8 years; 55.3% female). Higher BP SampEn during rest and stand was associated with increased risk of future recurrent falls (IRR=1.34, p=0.003, and IRR=1.22, p=0.044, respectively). Higher BP SampEn during recovery was associated with increased risk of future syncope (IRR=1.84, p=0.041). In a sub-cohort of participants aged 65+, higher BP SampEn was associated with increased risk of future fear of falling (N=1552; IRR=1.25, p=0.037). All reported IRRs are per one unit of SampEn. Conclusion: This study reports significant associations between higher complexity in BP data during an active stand protocol and increased risk of future falls, syncope, and fear of falling over ten-year follow-up.